PERANCANGAN PROTOTYPE MEKANISME GERAKAN JARI JEMPOL UNTUK ROBOT TERAPI STROK - Riyas, Nur Abdi Abdillah; Jatisukamto, Gaguk; Muttaqin , Aris Zainul; Mulyadi , Santoso; Sutjahjono , Hary (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Stroke is a functional disorder of the nervous system due to obstruction of blood flow to the brain. Rehabilitation is an effort to restore the function of the nervous system to a better condition than its current condition. Rehabilitation is carried out routinely by therapists with continuous physical therapy exercises. Patients can practice anywhere and anytime without depending on the therapist's schedule with technology-based rehabilitation, namely using an exoskeleton robot. This research examines the design of the human thumb finger mechanism according to anthropometric data so that it is expected to function under the working system of the human hand. Analyzing the movement of the thumb design with the help of Ansys Rigid Body Dynamics software. Analysis position with Ansys 19 R1 simulation for Rigid Body Dynamic mode. The results of the joint movement values (linkage) of the joints (interphalangeal joint, IP), MCP (metacarpophalangeal), and (carpometacarpal joint, CMC) are as follows. The (interphalangeal joint) IP angle simulation results get an angle value of -40.30°, while the CMC angle gets an angle value of 65.90° and the MCP angle gets an angle value of 71.80°. In comparison, the IP angle of the human thumb has an angle of 80-90°, the CMC angle is 43-70° and the MCP angle is 50-71°.